Human Mesenchymal Stem Cell‐Derived Miniature Joint System for Disease Modeling and Drug Testing (Adv. Sci. 21/2022). Issue 21 (25th July 2022) - Li, Zhong; Lin, Zixuan; Liu, Silvia; Yagi, Haruyo; Zhang, Xiurui; Yocum, Lauren; Romero‐Lopez, Monica; Rhee, Claire; Makarcyzk, Meagan J.; Yu, Ilhan; Li, Eileen N.; Fritch, Madalyn R.; et al.
Abstract : Human Mesenchymal Stem Cell‐Derived Miniature Joint System In article number 2105909 by Rocky S. Tuan, Hang Lin, and co‐workers, a miniature synovial joint‐mimicking system (miniJoint) is established in a microfluidics‐enabled bioreactor, in which human mesenchymal stem cell‐derived bone‐cartilage complex, synovial‐like fibrous tissue, and adipose tissue are integrated and show active crosstalk. The data demonstrate the potential of miniJoint as a new model for the study of joint pathology and the development of novel therapeutic interventions.